2012
DOI: 10.1038/modpathol.2011.212
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocyte cilia are abnormal in syndromic and non-syndromic biliary atresia

Abstract: Biliary atresia is a neonatal disorder characterized by aggressive fibroinflammatory obliteration of the biliary tract. Approximately 20 percent of biliary atresia patients demonstrate left-right laterality defects (syndromic biliary atresia). Cilia participate in important physiologic functions in cholangiocytes, and since some ciliopathies have been associated with both laterality defects and hepatic fibrosis, we hypothesized that patients with syndromic biliary atresia exhibit abnormalities of cholangiocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 29 publications
9
56
0
Order By: Relevance
“…As for the left-right laterality and cilia formation [which were speculated to be closely associated with congenital biliary atresia in humans (Nakanuma et al, 2010;Chu et al, 2012)], no appreciable defects in both laterality (data not shown) and cilia formation in gallbladder/bile ducts (supplementary material Fig. S7) were observed in Sox17 +/− embryos at 15.5-16.5 dpc.…”
Section: Research Article Biliary Atresia In Sox17 Mutantsmentioning
confidence: 84%
See 1 more Smart Citation
“…As for the left-right laterality and cilia formation [which were speculated to be closely associated with congenital biliary atresia in humans (Nakanuma et al, 2010;Chu et al, 2012)], no appreciable defects in both laterality (data not shown) and cilia formation in gallbladder/bile ducts (supplementary material Fig. S7) were observed in Sox17 +/− embryos at 15.5-16.5 dpc.…”
Section: Research Article Biliary Atresia In Sox17 Mutantsmentioning
confidence: 84%
“…In infants and children with biliary atresia, 10~20% of the fetal/embryonic type demonstrate left-right laterality defects, and some patients with the mutation in PKHD1, encoding the ciliary protein fibrocystin, are closely correlated with a ciliopathy with clinical features that resemble biliary atresia (Nakamura et al, 2010;Hartley et al, 2011). Moreover, cilia structure and distribution within bile ducts were previously shown to be affected in the specimens of human biliary atresia: shorter, abnormal orientation, and less abundant cilia in the biliary atresia specimens (Chu et al, 2012). These findings raise a possible association of the reduced Sox17 activity in the gallbladder primordium with the ciliopathy associated with congenital biliary atresia.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that extrahepatic cholangiocyte primary cilia are decreased in both human BA and the mouse RRV BA model (43, 44). For this reason, we examined cilia in primary neonatal mouse extrahepatic cholangiocytes treated with either biliatresone or the nontoxic isoflavanone-3 that copurifies with biliatresone.…”
Section: Resultsmentioning
confidence: 99%
“…Below the diaphragm, in addition to biliary tract anomalies, patients may present with midline or left-sided liver, polysplenia or asplenia, and interrupted inferior vena cava [40]. The laterality defects exhibited in biliary atresia splenic malformation syndrome are phenotypically similar to those observed in the ciliopathies, a heterogenous group of diseases caused by functional and structural defects in genes that encode cilia proteins [41,42,43,44,45,46,47,48]. Cilia are evolutionarily conserved, aid in establishing the left-right axis in vertebrates, and are present on many cell types, including the apical surface of cholangiocytes, where cilium function is integral to bile flow and bile ductular formation [49].…”
Section: Proposed Genetic Etiologies Of Biliary Atresiamentioning
confidence: 99%